A curved graphene nanoribbon with multi-edge structure and high intrinsic charge carrier mobility - Niu, Wenhui; Ma, Ji; Soltani, Paniz; Zheng, Wenhao; Liu, Fupin; Popov, Alexey A.; Weigand, Jan J.; Komber, Hartmut; Poliani, Emanuele; Casiraghi, Cinzia; Droste, Joern; Hansen, Michael Ryan; et al. (Journal of the American Chemical Society, 2020)
Structurally well-defined graphene nanoribbons (GNRs) have emerged as highly promising materials for the nextgeneration nanoelectronics. The electronic properties of GNRs critically depend on their edge topologies. Here, we demonstrate the efficient synthesis of a curved GNR (cGNR) with a combined cove, zigzag, and armchair edge structure, through bottom-up synthesis. The curvature of the cGNR is elucidated by the corresponding model compounds tetrabenzo[a,cd,j,lm]perylene (1) and diphenanthrene-fused tetrabenzo[a,cd,j,lm]perylene (2), the structures of which are unambiguously confirmed by the X-ray singlecrystal analysis. The resultant multi-edged cGNR exhibits a well-resolved absorption at the near-infrared (NIR) region with a maximum peak at 850 nm, corresponding to a narrow optical energy gap of ∼1.22 eV. Employing THz spectroscopy, we disclose a long scattering time of ∼60 fs, corresponding to a record intrinsic charge carrier mobility of ∼600 cm2 V-1 s-1 for photogenerated charge carriers in cGNR.
CRIS-Team Scopus Importer:2023-03-20